Combination of upstream primer-multuplex PCR (UP-mpcr) and capillary electrophoresis for equine genetic analysis (Mongolian Journal of Agricultural Sciences, 2023)
The purity and content of DNA extracted from the sample is important during PCR analysis. In the conditions of our country, there are many cases of working on samples that do not meet the requirements for some reason. In such cases, there is a need to further test and develop other sensitive methods. The upstream-primer multiplex PCR (UP-mPCR technique) is known for its high specificity and fidelity, and has been used for detecting multiple food borne pathogens, meat species testing and detecting different genetically modified organism (GMO) insertions in a plant genome. The purpose of this experiment is to apply the UP-mPCR method on DNA samples that do not meet the quality requirements, and to test it on domestically produced diagnostics.We combined UP-mPCR with fragment analysis on DNA capillary electrophoresis genetic analyzer by applying fluorescent labelled upstream primers which were tested by amplifying 8 STRs on 23 low-quality equine gDNA samples. These samples had formerly undergone unsuccessful testing by domestic equine genotyping 15-plex kit. Single trial of UP-mPCR on the same samples showed successful amplification and detection of amplicons from 4-6 STRs, and their alleles were genotyped. Combining UP-mPCR and DNA capillary electrophoresis can be helpful in extreme situations such as having limited amounts of sample, or a shortage of multiple fluorescent dye oligonucleotides. There is no former report about the same method as combining UP-mPCR with fragment analysis.